Implementation issues of vehicular ad hoc network applications: selected case studies in Malaysia - Muhammed Yusof, Zulkefli; Mat Zin, Nur Nazmah; S. Baharun, Nor Hanini; M Khairi, Nur Syahirah (2013)
This paper looks into the implementation issues on Vehicular Network applications. In order to have better insights two scenarios have been chosen and simulated. A toll booth system shows the issues on a hybrid VANET application while City Taxi system provides the studies of highly mobile applications.